Penyelesaian Sengketa Lahan Hutan Melalui Proses Mediasi - Riska Fitriani (Fakultas Hukum Universitas Riau, 2012)
Disputes out of court settlement is also called Alter-native Dispute Resolution (ADR). One dispute isbetween the investor and the community in the Districtof Kerinci Siak Kanan. Settlement is done by nego-tiation efforts, that is the process of negotiating orbargaining a concession, on the problems that arisein the community.